EFFECT OF USING TiO2 IN DYEING PROCESS TO LIQUID WASTE AND CHARACTERIZATION GLOVE LEATHER - Arya Prastyawan; Laili Rachmawati; Heru Budi Susanto (Berkala Penelitian Teknologi Kulit, Sepatu, dan Produk Kulit, 2024)
This study aims to reduce the use of kronos (content of TiO2 ³92,5%) to overcome the problem of dyeing liquid waste turbidity at PT Adi Satria Abadi, Yogyakarta. In this study, the characteristics of glove leather resulting from reducing the number of kronos were also looked at. Post tanning process in wet blue sheepskin consist of: wetting back, dyeing, retanning, fatliquoring, fixing I, top fatliquoring, dan fixing II. The study is carried out in the dyeing process, and it was divided into 3 treatments. Treatment I used 1.5% kronos, treatment II used 1% kronos, and the control used 2% kronos (PT Adi Satria Abadi standards). The turbidity of the liquid waste from the dyeing process, the organoleptic and physical characteristics of glove leather were tested. The organoleptic test results for skin characteristics obtained from treatment I were compared with the control: evenness of color (very suitable), color match (suitable), defect covering (very suitable), and softness (very suitable). Meanwhile, the results obtained from treatment II were compared with the control: color evenness (very suitable), color match (quite suitable), defect covering (not suitable), and softness (very suitable). The results of physical tests on skin thickness and softness between control, treatment I and treatment II showed results that met the standards. The skin rubbing test result in treatments I and II was better than the control. The turbidity of dyeing waste shows that treatment I produces lower turbidity than treatment II, while treatment II shows a lower level of waste turbidity than the control. It was concluded that treatment I produced waste with lower turbidity than the control and produced glove leather characteristics that met PT Adi Satria Abadi standards.